(untitled) (Journal of Universal Science Research, 2025)
This article explores the mythological and folkloric roots that permeate J.K. Rowling’s Harry Potter series, highlighting the author’s deep engagement with ancient literary traditions across various cultures. By examining the origins of character names and thematic elements, the article demonstrates how Rowling integrates motifs from Greek, Roman, Norse, Celtic, Egyptian, and Indian mythology to enrich her fantasy world. Characters such as Hermione Granger and Nagini are shown to embody attributes of their mythological counterparts, while legendary figures like Merlin and Morgana anchor the magical universe in well-known folklore. The study emphasizes that Rowling’s fusion of ancient myths with contemporary storytelling not only enhances the depth and resonance of her characters but also serves as a bridge between classical literature and modern fantasy. Ultimately, this analysis underlines the timeless relevance of myth and its vital role in shaping the narrative and symbolic structure of Rowling’s work.